A review of the current management of acute and chronic heart failure in the context of ischemic heart disease. Issue 1 (March 2017) - Brown, P. F.; Thambyrajah, J.
Abstract: Heart failure secondary to left ventricular systolic dysfunction is a prevalent condition across Europe with ischemic heart disease the most common etiology. Acute heart failure is a medical emergency and management comprises diuretics and vasodilators. Several alternative intravenous treatments have been trialed in recent years but no mortality benefit has been found with these agents. For chronic heart failure there are several well‐characterized disease‐modifying treatments available which include beta blockers, ACE inhibitors, mineralocorticoid antagonists, and device therapy. Sacubitril/valsartan is a novel therapy that has recently been demonstrated to have additional prognostic benefit. Answer questions and earn CME: https://wileyhealthlearning.com/Activity2/5222693/Activity.aspx